2018
DOI: 10.20944/preprints201802.0028.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outflow Enhancement by Three Different ab Interno Trabeculectomy Procedures in a Porcine Anterior Segment Model

Abstract: Objective: To evaluate three different microincisional ab interno trabeculectomy procedures in a porcine eye perfusion model. Methods:In perfused porcine anterior segments, 90 degrees of trabecular meshwork (TM) were ablated using the Trabectome (T; n=8), Goniotome (G; n=8), or Kahook device (K; n=8). After 24 hours, additional 90 degrees of TM were removed. Intraocular pressure (IOP) and outflow facility were measured at 5 µl/min and 10 µl/min perfusion to simulate an elevated IOP. Structure and function were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Both increased age and reduced TM cellularity are a major risk factor for the development of glaucoma. On the other hand, partially removing TM cells can also reduce IOP at least temporarily 47 , while excision of TM causes a profound and lasting IOP drop ex vivo 27,48 and clinically 49 . Abu-Hassan et al 23 recently showed that the transplantation of human TM cells or TM-like iPSCs into the anterior segment perfusion model can restore outflow after killing about 1/3rd of TM cells with saponin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both increased age and reduced TM cellularity are a major risk factor for the development of glaucoma. On the other hand, partially removing TM cells can also reduce IOP at least temporarily 47 , while excision of TM causes a profound and lasting IOP drop ex vivo 27,48 and clinically 49 . Abu-Hassan et al 23 recently showed that the transplantation of human TM cells or TM-like iPSCs into the anterior segment perfusion model can restore outflow after killing about 1/3rd of TM cells with saponin.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo perfused anterior segment models from a range of species have been used to examine and manipulate the TM function [20][21][22][23][24][25][26] because there is a scarcity of whole human donor eyes for research. In contrast, TM cells from corneal rims used for corneal transplantation, TM-removal surgeries, and TM cell lines, are more readily available 27,28 and could lend themselves to scalable studies when seeded into decellularized anterior segment scaffolds from pig eyes. As done in other tissues in research [29][30][31][32][33][34] and medical applications [35][36][37][38] , removal of cells from ECM can provide a bioartificial scaffold for recellularization with cells of choice.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the IOP that AIT can achieve is limited by the episcleral venous pressure of 8 mmHg [17], yet most studies report IOPs around 15 mmHg. In contrast, TRAB can achieve very low IOPs, even below episcleral venous pressure, and eliminate drops [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The advantages of a clear angle view and anterior chamber stability have recently become more readily available with an I&A-equipped dual-blade (Goniotome, Neomedix Corp., Tustin, California, United States) that does not require a high-frequency generator to molecularize the TM and instead excises a strip. 14,18 These features and its ability to excise TM in a controlled environment and to harvest it non-destructively make it also useful for glaucoma research.…”
Section: Introductionmentioning
confidence: 99%
“…19 In the present study, we hypothesized that trabecular excision with an I&A-equipped dual-blade device could also restore outflow by removing the pathology. We have extensive experience studying outflow in experimental systems, 20,21 including gene transfer, [22][23][24][25][26][27][28] disease modeling 5,7,19 and surgical outflow enhancement, 14,15,18,[29][30][31][32] but this is the first study of a microsurgical intervention for glaucoma in an ex vivo model of glaucoma.…”
Section: Introductionmentioning
confidence: 99%